PREVALENCE, RISK FACTORS, MANAGEMENT, OUTCOMES, AND PREDICTORS OF MORTALITY IN RETROPERITONEAL HEMATOMA AFTER PERCUTANEOUS CORONARY INTERVENTION - SAOOD , Y; ASIM , M; SALMAN , A; KHAN , MI; ZAFAR , R; KAZMI , SIA (Biological and Clinical Sciences Research Journal, 2023)
The development of complications related to femoral artery puncture continues to be frequent following contemporary percutaneous coronary intervention (PCI). The basic aim of the study is to find retroperitoneal hematoma after percutaneous coronary intervention prevalence, risk factors, management, outcomes, and predictors of mortality. This retrospective cohort study was conducted at the Peshawar Institute of Cardiology, Peshawar, from January 2022 to April 2023. The study population consisted of patients who underwent PCI procedures. Sixty-eight patients who developed RPH after PCI were included in the analysis. Demographic information such as age, gender, and relevant baseline characteristics of the patients was recorded. Clinical variables encompassed comorbidities (e.g., hypertension, diabetes mellitus), the indication for PCI (e.g., stable angina, acute coronary syndrome), and procedural details, including the access site and anticoagulant medications. Data was collected from 68 patients. The mean age of patients who developed RPH was 63.7 years, ranging from 45 to 78 years. Gender distribution showed 60% male and 40% female patients. Common comorbidities among this cohort included hypertension (80% of cases) and diabetes mellitus (45% of cases). The study identified several risk factors associated with the development of RPH post-PCI, including female gender (p < 0.05), anticoagulant use (p < 0.01), and hypertension (p < 0.05), which demonstrated a statistically significant association. Based on the results, the study provides valuable insights into the prevalence, risk factors, management strategies, clinical outcomes, and predictors of mortality associated with RPH following PCI.